2009
DOI: 10.1002/jcp.21859
|View full text |Cite
|
Sign up to set email alerts
|

E2F4 expression is required for cell cycle progression of normal intestinal crypt cells and colorectal cancer cells

Abstract: The generation of knock-out mice for E2F4 gene expression has suggested a role for this transcription factor in establishing and/or maintaining the intestinal crypt compartment. Having previously demonstrated that E2F4 is cytoplasmic in quiescent-differentiated cells but nuclear in growth factor-stimulated proliferative cells, the present study was aimed at determining the role of E2F4 in the control of human intestinal epithelial proliferation. Results herein demonstrate that lentiviral infection of an shRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 69 publications
5
72
0
2
Order By: Relevance
“…Although E2F4 has been particularly described as a repressor of both transcription and cell cycle progression (Vairo et al, 1995;Muller et al, 1997;Rayman et al, 2002), several studies have reported other roles such as 1-its binding to E2F-responsive elements as a pocket protein-free E2F during S phase, 2-its capacity to induce E2F target genes and 3-its implication in proliferation. Hence, these studies suggest that E2F4 can also act as a transcriptional activator (Verona et al, 1997;Wells et al, 1997;Ross et al, 1999;Lang et al, 2001;Garneau et al, 2009;van Amerongen et al, 2009). For example, studies carried out by Lo et al, 2011 demonstrated that the majority of E2F4 binding sites are located proximal to transcription start sites.…”
Section: Functionmentioning
confidence: 95%
See 4 more Smart Citations
“…Although E2F4 has been particularly described as a repressor of both transcription and cell cycle progression (Vairo et al, 1995;Muller et al, 1997;Rayman et al, 2002), several studies have reported other roles such as 1-its binding to E2F-responsive elements as a pocket protein-free E2F during S phase, 2-its capacity to induce E2F target genes and 3-its implication in proliferation. Hence, these studies suggest that E2F4 can also act as a transcriptional activator (Verona et al, 1997;Wells et al, 1997;Ross et al, 1999;Lang et al, 2001;Garneau et al, 2009;van Amerongen et al, 2009). For example, studies carried out by Lo et al, 2011 demonstrated that the majority of E2F4 binding sites are located proximal to transcription start sites.…”
Section: Functionmentioning
confidence: 95%
“…Accordingly, forced expression of nuclear E2F4 promotes S-phase entry into cardiomyocytes (Ebelt et al, 2005;van Amerongen et al, 2009). Moreover, nuclear E2F4 expression is associated with proliferation of rapid renewing tissues such as bone marrow (Kinross et al, 2006;Zhang et al, 2010), digestive tract (Rempel et al, 2000;Garneau et al, 2009) and skin (Wang et al, 2000;Wang et al, 2001). Many in vivo and in vitro studies have led to the identification of numerous roles of E2F4 in different cellular processes such as nervous system development, intestinal homeostasis, bone development, myogenesis, adipogenesis and erythropoiesis, to name a few.…”
Section: Functionmentioning
confidence: 99%
See 3 more Smart Citations